2020
DOI: 10.24014/konfigurasi.v4i2.9394
|View full text |Cite
|
Sign up to set email alerts
|

Desain dan Uji Coba Media Pembelajaran Alat Peraga Penjernihan Air Sederhana Berorientasi Green Chemistry Pada Materi Koloid di SMA Negeri 1 Pekanbaru

Abstract: This research was instigated by the unavailability of the instructional media implementing green Chemistry concept and the limitation of laboratory facilities at State Senior High School 1 Pekanbaru.  It aimed at knowing the validity and practicality levels of Green Chemistry oriented Simple Water Purifier prop instructional media on Colloid lesson, the guidebook of constructing and using props.  It was Research and Development (R&D) with 4D development model.  The technique of collecting the data was ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of an interview conducted with one of the chemistry teachers suggested that chemistry learning is more dominated by teachers than students (Anggreani, 2019). The results of the literature study also found that practicum activities still need to be carried out (Rahmawati & Khamidinal, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…The results of an interview conducted with one of the chemistry teachers suggested that chemistry learning is more dominated by teachers than students (Anggreani, 2019). The results of the literature study also found that practicum activities still need to be carried out (Rahmawati & Khamidinal, 2019).…”
Section: Introductionmentioning
confidence: 98%